PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. INDAKO KRAKATAU - Tania, Keely; Tanesa, Gerry (EDUTECH CONSULTANT, 2018)
This research approach is based on a quantitative approach. This type of research is a quantitative descriptive study. The nature of this research is causal. The population in this study were all employees of PT Indako Krakatau, Medan, as many as 60 people were taken in 2017. To determine the number of samples, researchers used the Slovin formula and obtained as many as 52 employees. Data collection techniques are carried out by interviews, questionnaires, and documentation studies. Sources of data needed in this study are primary data and secondary data. The results of the study on the hypothesis indicate that work motivation has a positive and significant effect on employee performance at PT Indako Krakatau. Work discipline partially has a positive and significant effect on employee performance at PT Indako Krakatau. Work motivation and work discipline simultaneously have a positive and significant effect on employee performance at PT Indako Krakatau. 59.8% of the performance of PT Indako Krakatau employees can be explained by work motivation-free variables and work discipline while the remaining 40.2% is explained by other independent variables not examined in this study such as career development, training, leadership, and others.